Assessment of procurement processes in lower Local Government Authority (LLGA’s evidences from Kilimanjaro and Manyara (LLGAs) - Bayo, Rose R. (Mzumbe University, 2024)
A Dissertation Submitted to the School of Business in Partial/Fulfillment of the Requirements for Award of the Master of Procurement and Supply Chain Management of Mzumbe University 2016.